2021
DOI: 10.7554/elife.68911
|View full text |Cite
|
Sign up to set email alerts
|

A projectome of the bumblebee central complex

Abstract: Insects have evolved diverse and remarkable strategies for navigating in various ecologies all over the world. Regardless of species, insects share the presence of a group of morphologically conserved neuropils known collectively as the central complex (CX). The CX is a navigational center, involved in sensory integration and coordinated motor activity. Despite the fact that our understanding of navigational behavior comes predominantly from ants and bees, most of what we know about the underlying neural circu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…The same study also outlined how a short-term memory of a desired heading could be maintained in the FB of the CX via synapse-weight modulation after the original guidance cue is removed that could support the wind compensation and backtracking behaviours described above. Our model hypothesises the existence of a ring attractor network to optimally integrate the desired heading cues which we suggest could be realised in the complex intra-connections within the FB and the NO ( Hulse et al, 2021 ; Sayre et al, 2021 ). We also hypothesise that different populations of Protocerebral bridge - Fan-shaped body - Nodulus (PFN) neurons in the CX simultaneously store the distinct desired headings computed by the independent navigation systems (e.g.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The same study also outlined how a short-term memory of a desired heading could be maintained in the FB of the CX via synapse-weight modulation after the original guidance cue is removed that could support the wind compensation and backtracking behaviours described above. Our model hypothesises the existence of a ring attractor network to optimally integrate the desired heading cues which we suggest could be realised in the complex intra-connections within the FB and the NO ( Hulse et al, 2021 ; Sayre et al, 2021 ). We also hypothesise that different populations of Protocerebral bridge - Fan-shaped body - Nodulus (PFN) neurons in the CX simultaneously store the distinct desired headings computed by the independent navigation systems (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…We also hypothesise that different populations of Protocerebral bridge - Fan-shaped body - Nodulus (PFN) neurons in the CX simultaneously store the distinct desired headings computed by the independent navigation systems (e.g. PI-based home vector is stored in CPU4 neurons [a subset of PFNs]; Stone et al, 2017 ; Hulse et al, 2021 ; Sayre et al, 2021 ). Further, the hypothetical context switching introduced could be achieved by the recently mapped FB-NOc neurons found in the bees ( Sayre et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we enabled the addition of connections among CL2 neurons of the same hemisphere during the optimization process. Projection patterns suggest that all CL2 neurons of the same hemisphere branch in the lower unit of the contralateral NO, like P-EN neurons in Drosophila (Wolff et al, 2015) and the bumblebee (Sayre et al, 2021). Optimization converged at a solution with excitatory and inhibitory connections among CL2 neurons branching in the same nodulus.…”
Section: Resultsmentioning
confidence: 99%
“…Franconville et al (2018) reported that connections from E-PG onto P-EN neurons in the PB are mediated by ∆7 neurons. As TB1 and TB2 neurons cross the midline of the locust PB, they are, in addition to contralateral processes observed in some CL1 neurons innervating the innermost columns of the PB (Sayre et al, 2021), candidates for mediating ring closure. An internal compass representation must adapt to a new heading direction when the animal turns.…”
Section: Discussionmentioning
confidence: 99%